Male and Female Buying Decision Making Processes Seen From BlackBerry Messenger Texts - Deviana Stefani Haryanto; Jusuf I Ibrahim (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
This study observes the male and female buying decision making processes seen from BlackBerry Messenger texts. It focuses on the way of how male and female customers make a buying decision in the online shop via BlackBerry Messenger. The data are analyzed by using the theory of the consumer decision-making process by Lamb, Hair, McDaniel (2003) which includes five stages. I found that the female customers have almost two times total more than male customers in the four stages in consumer decision making process. It means, the male decision-making seems to be rational, fast, and attentive for product quality and its function. However, the female decision-making is more emotional, attentive for product surface or outside appearance, and careful for choosing a product she wants to buy. Overall, I know that gender is an important factor that makes the buying processes between both gender groups different.